The Role of Digital Literacy in Islamic Religious Education Learning in the Technology Era at MAN 3 Banyuwangi - Suhilmiati, Endhang; Hanika, Ita Musfirowati; Hardiyanti, Nurul Rida; Jejen, Atep; Sutiapermana, Aden (International Journal of Educational Research Excellence (IJERE), 2024)
Islamic education is an important aspect of the MAN 3 Banyuwangi curriculum, which is now faced with challenges and opportunities with the development digital technology. In this era, digital literacy is becoming a crucial factor in facilitating the Islamic religious learning process in schools. Study This aim is to deepen the role deep digital literacy context learning Islamic religious education at MAN 3 Banyuwangi. With a qualitative approach, research This utilizes interviews, observations, and analysis content to explore how digital literacy influences and is implemented in Islamic religious learning in schools. Findings from the study This discloses that digital literacy plays an important role in increasing the quality of Islamic religious learning at MAN 3 Banyuwangi. Teachers use various digital resources, such as learning videos and Islamic religious websites, to enrich their experience. Study, student. Students are also actively using technology to look for information and discussion about the Islamic religion. However, there are also challenges related to accessibility, technology, and the development of digital literacy skills among students. This study also highlights the importance of integrating technology into the curriculum of Islamic religious education at MAN 3 Banyuwangi. By utilizing digital literacy effectively, schools can increase understanding and experience. Study students related to the Islamic religion. Study This contributes to our understanding of how technology can be used to enrich Islamic religious learning at MAN 3 Banyuwangi, as well as the associated challenges and strategies with the integration deep digital literacy in Islamic education.